INCLUSION OF DISABLED PERSONS IN THE REPUBLIC OF MACEDONIA: Social Protection and Employment Policies - Trbojevik, Svetlana; Bogoevska, Natasha (Ревија за социјална политика/Journal of Social Policy, 2015)
Social protection is determined as an activity of public interest.The state implements the social protection of citizens in accordance withthe principle of social justice. The social protection is defined as a systemof measures, activities and policies for prevention and overcoming thebasic social risks to which the citizen is exposed throughout life, forreducing poverty and social exclusion and for strengthening citizen’scapacity for self protection.